2021
DOI: 10.3390/mps4040076
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Body Therapies for Cancer Patients Living with Depression, Anxiety or Insomnia (MIRACLE): A Systematic Review with Individual Participant Data Network Meta-Analysis

Abstract: Depression, anxiety, and insomnia are common in cancer patients. Mind-body therapies (MBTs) are promising forms of treatment for cancer patients living with depression, anxiety, and insomnia. The objective of this study is to assess the effectiveness and acceptability of MBTs in cancer patients living with depression, anxiety, or insomnia. EMBase, PubMed, Cinahl, PsychINFO, IndMED, CSI-NISCAIR, CNKI, Clinicaltrial.gov, ChiCTR, and CTRI will be searched until October 2020 for relevant studies. Randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 82 publications
0
4
0
2
Order By: Relevance
“…Implications for holistic practice, across all populations and especially those caring for patients with chronic illness, are to encourage a healthy lifestyle, which mitigates the effects of anxiety and promotes a sense of well-being. In terms of this study's results, nurses could direct women with breast cancer to engage and sustain their yoga practice which would benefit them, both psychosocially and physically 39,40. It was surprising, yet reassuring, that despite having had a breast cancer diagnosis, participants of the survey viewed themselves overall as healthy, describing their health as either “very good” or “good.” No participant reported their health as “poor” or “bad.” Future research is needed to elucidate modifiable factors that contribute to breast cancer survivors' perceptions of themselves as healthy.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Implications for holistic practice, across all populations and especially those caring for patients with chronic illness, are to encourage a healthy lifestyle, which mitigates the effects of anxiety and promotes a sense of well-being. In terms of this study's results, nurses could direct women with breast cancer to engage and sustain their yoga practice which would benefit them, both psychosocially and physically 39,40. It was surprising, yet reassuring, that despite having had a breast cancer diagnosis, participants of the survey viewed themselves overall as healthy, describing their health as either “very good” or “good.” No participant reported their health as “poor” or “bad.” Future research is needed to elucidate modifiable factors that contribute to breast cancer survivors' perceptions of themselves as healthy.…”
Section: Discussionmentioning
confidence: 88%
“…In terms of this study's results, nurses could direct women with breast cancer to engage and sustain their yoga practice which would benefit them, both psychosocially and physically. 39,40 It was surprising, yet reassuring, that despite having had a breast cancer diagnosis, participants of the survey viewed themselves overall as healthy, describing their health as either "very good" or "good." No participant reported their health as "poor" or "bad."…”
Section: Implications For Nursing Practice and Researchmentioning
confidence: 99%
“…Specifically, mind-body therapies (MBTs), such as mindfulness and tai chi qigong (TCQ), have been studied and implemented in clinical practice to help patients and survivors of cancer manage unwanted, illness-related psychological and physical symptoms. 3 Reviews of the current literature show that outcomes from MBTs, such as mood and sleep quality, produce clinically significant, large effects, 3 - 5 therefore supporting their value as a clinical service for the cancer population. While some of these interventions are offered online or digitally, most MBT therapies are conducted in-person, and there is currently uncertainty as to whether in-person or online modalities are better suited for certain populations or specific MBTs.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of death anxiety in 1179 patients with advance cancer, concluded, “Therapies of short duration incorporating spiritual well-being and those evoking a sense of meaning were claimed to be the most beneficial, despite lacking rigorous statistical analysis” [ 47 ]. Another systematic review on psychedelics, covering 1850 records and 33 articles, stated, “Recent (controlled) trials with LSD, psilocybin, ketamine, and MDMA are of higher methodological quality and indicate positive effects on existential and spiritual well-being, quality of life, acceptance, and reduction of anxiety and depression with few adverse and no serious adverse effects.” [ 48 ] Birling et al have reviewed Mind-Body Therapies for Cancer Patients Living with Depression, Anxiety or Insomnia [ 49 ]. These therapies improve health through mindfulness, breathing exercises, postures, movements, and relaxation.…”
Section: Adhyatmachikitsa : Spiritual and Consciousness Rese...mentioning
confidence: 99%